Business Model of Insurance Technology Company in Indonesia (Case Study on Premiro.com) - Rahadian, Dadan; Krisnawati, Astrie; Sulistio, Farrastya Ayuningrum (East Asian Journal of Multidisciplinary Research, 2024)
The rapid increase in internet usage in Indonesia has fueled the rise of Insurtech, addressing low literacy, inclusion, and insurance penetration levels. Insurtech companies are pivotal in offering digital-based insurance services to increase insurance users. This research examines the business models employed by Indonesian Insurtech firms, focusing on a case study of Premiro.com. The study also aims to identify the strengths that provide these companies with competitive advantages. Utilizing a descriptive research methodology and a qualitative approach, the research includes interviews and secondary data collection through literature reviews and company information. The analysis employs the Business Model Canvas and Value Design Model frameworks. The study details Premiro's business model elements: customer segments, value proposition, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. It also examines value drivers, nodes, exchanges, and extracts. Findings reveal Premiro's strength lies in its lean and efficient cost structure. The study offers practical recommendations for Premiro to enhance operational effectiveness, expand market share, and boost competitiveness.